2022
DOI: 10.3389/fphar.2022.890732
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Brolucizumab for the Treatment of nAMD: A Systematic Review and Meta-Analysis

Abstract: Introduction: As demonstrated in pivotal clinical trials, brolucizumab can be used to treat neovascular age-related macular degeneration (nAMD) because it antagonizes vascular endothelial growth factor (VEGF) in the vitreous. However, brolucizumab may cause retinal vasculitis obliterans in the presence of inflammation in the eyes. In the present study, a meta-analysis of randomized controlled trials (RCTs) was conducted to evaluate the efficacy and safety of brolucizumab.Methods:ClinicTrail.gov., Embase, Cochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…They found that brolucizumab-treated eyes exhibited a greater reduction in thickness at 1, 3, 6, 9, and 12 months postinjection compared with aflibercept. 58 These findings are consistent with several case series, which also reported significant decreases in CST. 42,44 Enriquez et al 44 reported 50 eyes that experienced complete fluid resolution after a single injection.…”
Section: Real-world Data Perspective On Adverse Events and Intraocula...supporting
confidence: 92%
See 4 more Smart Citations
“…They found that brolucizumab-treated eyes exhibited a greater reduction in thickness at 1, 3, 6, 9, and 12 months postinjection compared with aflibercept. 58 These findings are consistent with several case series, which also reported significant decreases in CST. 42,44 Enriquez et al 44 reported 50 eyes that experienced complete fluid resolution after a single injection.…”
Section: Real-world Data Perspective On Adverse Events and Intraocula...supporting
confidence: 92%
“…Regarding modification of dosing or administration frequency to improve safety outcomes, a recent meta-analysis evaluating 6 RCTs and 3574 patients revealed that there is no significant difference between brolucizumab 6 mg and 3 mg dosing regarding serious adverse events and serious ocular adverse events. Brolucizumab was more likely to lead to severe ocular adverse events compared with aflibercept and ranibizumab (odds ratio: 2.15, 95% CI: 1.11–4.16; P = 0.02) 58. Notably, the study did not delineate between types of serious ocular events, so specific conclusions about IOI, RV, and RVO cannot be drawn.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations